PENERAPAN PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING ( CTL ) UNTUKMENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IIIB SDN 59 SEBANGAR KECAMATANMANDAU KABUPATEN BENGKALIS - Widia Ningsih; Erlisnawati Erlisnawati; syahrilfuddin syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the student achievement of social studies fifth graderes SDN 011 Banjar XII still low with an average value of 55,25 and minimum completenness criteria (KKM) social studies is 65. Between students, amounting to 20 people only 8 students who achieve classical KKM with 40%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of cooperative learning model type Numbered Heads Together (NHT) can improve students achievment of social studies at SDN 011 Banjar XII. The research was conducted on march 18, 2014 to april 17, 2013by 2 cyclees. Subjects were students of SDN 011 Banjar XII, totalling 20 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning models obtained results koopertif NHT type of activity the teacher in the lerning process in cycle I frist meeting was 58,3% and at the second meeting of teacher activity increased by 12,5% to 70,8%. cycle II firs meeting and the second meeting of activity increased by 12,5% to 83,3% and the second meeting of activity increased by 12,5% to 95,8%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 54,2% and at second meeting of activity increased 8,3% to 62,5%% and a second meeting of activity increased 16,7% improve to 79,2%. At the firs meeting of the second meeting of activity increased 12,5% to 91,7%%. This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 55,25. In the first cycle improve an average of 69,75 with increase as 26,24% and an impove in the second with an average of 81,75 with increase as 47,96%. Result in the research that the implementation of cooperative learning model of Numbered Heads Together (NHT) can improve students achievement of social Studies at fifth graderes SDN 011 Banjar XII Kecamatan Tanah Putih.Key Words : Model Contextual Teaching And Learning (CTL), Fave graderes students Achievement.